District Education Department (PPD) Officials and Commitment to Change Practice - Azmi, Azerai; Hamzah, Mohd Izham Mohd; Hamzah, Mohd Izham Mohd; Nor, Mohamed Yusoff Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Various efforts have been devised to plan educational changes such as the District Transformation Program as outlined in the Malaysian Education Development Plan 2013-2025. The District Education Department (PPD) officials are consistently committed to implementing these changes. The research is aimed to identify the level of implementation of the PPD Transformation Program, the level of commitment to change practices and to identify differences in the commitment to change practices based on the demographics of the PPD’s officials. Descriptive survey method was used to gather information on the dimensions of the implementation of the PPD Transformation Program and commitment to change practices, while inferential survey was used to identify differences in commitment to change practices from the dimensions of affective commitment, continuation commitment and normative commitment based on demographics of PPD’s officials. A total of 400 respondents comprising of education services personnel from 13 PPDs in Malaysia were randomly selected. The findings indicate that the level of transformation of PPD is at a very high level of implementation whereby the guidance management and mentoring dimension indicates the highest score (mean= 4.43; SD=.26), followed by the enculturation dimension (mean=4.41; SD=.23), new goal setting dimension (mean=4.38; SD=.25) and restructuring dimension (mean=4.36; SD=.22). Next, commitment to change practices for affective commitment dimension is at a very high level (mean=4.42; SD=.33), meanwhile, continuation commitment dimension (mean=4.14; SD=.42) and normative commitment (mean=4.29; SD=.35) are at a very high level. The findings also indicate that there is no significant difference between commitment to change practices based on the demographics of PPD officials. The findings of this research show that PPD officials are fully committed to change management regardless of age, academic qualifications, work experience at PPD and training attendance in relation to PPD Transformation Program.